Effectiveness of Narcotics Crime Assessment At the National Narcotics Agency of Badung Regency - I Dewa Gede Dwitya Giri Arta; I Nym Gd Sugiartha; I wayan Rideng (Journal Equity of Law and Governance, 2025)
The problem of narcotics has become a very concerning problem in Indonesia in Bali in particular. The National Narcotics Agency is one of the institutions authorized to deal with narcotics problems and rehabilitate narcotics addicts. It is hoped that rehabilitation of narcotics addicts can reduce narcotic problems. Assessment Arrangement and Implementation of Rehabilitation by the National Narcotics Agency of Badung Regency. The research method used in the assessment arrangement and the impact of assessment in narcotics crimes is an empirical method. The goal to be achieved in this study is to find out how effective the assessment of narcotics crimes in the National Narcotics Agency of Badung Regency. The results showed that the implementation of assessments at the Badung Regency National Narcotics Agency has not been effective because the judge's decision still has not used the results of the Recommendations of the Integrated Assessment Team in consideration of the determination of the verdict. Judges are still inclined to sentence prison confinement to defendants without considering sanctioning in the form of rehabilitation measures on the accused for recovery from narcotics snares.